Development of a fluorescent quantum dot-mycolic acid probe for use in Mycobacterium tuberculosis antibody detection - Forbes, Patricia B.C. (University of Pretoria, 2022)
Thesis (PhD (Chemistry))--University of Pretoria, 2022.